Current status of life cycle cost practice in Malaysian construction industry - Ayob, Mohd Fairullazi; Abdul Rashid, Khairuddin (IIUM Press, 2016)
In this paper, our aim is to report the state and practice of LCC in the Malaysian construction industry. In preparing this paper, a comprehensive review of literature on the practice of LCC related to Malaysian construction industry were conducted. The outcomes of the review will be reported as an introduction of the research. The LCC assessment can be divided into three categories which are data inputs, conversion and outputs (BS ISO 15686, 2008; Kelly et al., 2009; RTO-SAS-069, 2009). Nevertheless, it was observed from the literature review the main focus on the LCC practice in Malaysia is considerably on the conversion of LCC analysis. Most of the literatures written on LCC give emphasis to conversion, but less focus is given to the data input and outputs of LCC analysis. Indeed, there is no research has been carried out to identify of how the data inputs are utilized for conversion in producing accurate and reliable outputs of the LCC analysis. Besides, there is no research has been performed to ascertain whether the local data inputs are appropriate to be used in monitoring the outputs of LCC analysis.